Kyrgyz Republic : Ex Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Ex Post Assessment of Longer-Term Program Engagement for the Kyrgyz Republic explains macroeconomic and structural performance. External debt service claimed a steadily increasing share of fiscal revenues, but a strengthened commitment to prudent fiscal policies and improved policy capacity have helped to turn around macroeconomic performance. Fiscal policy must deliver on its revenue targets, while addressing poverty and servicing large external debt obligations. Debt reduction must continue to be a main objective of any IMF-supported program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet